2009
DOI: 10.1631/jzus.b0820179
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Salvia miltiorrhizae on the hearts of rats with severe acute pancreatits or obstructive jaundice

Abstract: Abstract:Objective: To investigate the therapeutic effects and mechanisms of Salvia miltiorrhizae (Danshen) in the treatment of severe acute pancreatitis (SAP)-or obstructive jaundice (OJ)-induced heart injury. Methods: A total of 288 rats were used for SAP-(n=108) and OJ-associated (n=180) experiments. The rats were randomly divided into sham-operated, model control, and Salvia miltiorrhizae-treated groups. According to the difference of time points after operation, SAP rats in each group were subdivided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Sham-operateds were performed just by moving the pancreas and duodenum after opening the abdominal cavity. Fifteen minutes after successful operation, a single dose of Salvia miltiorrhizae injection (dosage 0.4 ml/100 g body weight [30][31][32]) was given via femoral vein to rats in the treated groups while equal volume of physiological saline solution was used in the sham-operated and model control group. Continuous infusion of physiological saline solution using a microinjection pump was then maintained until the end of the 3-, 6-and 12-h observation period in the corresponding groups.…”
Section: Preparation Of Animal Models and Associated Therapeutic Regimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Sham-operateds were performed just by moving the pancreas and duodenum after opening the abdominal cavity. Fifteen minutes after successful operation, a single dose of Salvia miltiorrhizae injection (dosage 0.4 ml/100 g body weight [30][31][32]) was given via femoral vein to rats in the treated groups while equal volume of physiological saline solution was used in the sham-operated and model control group. Continuous infusion of physiological saline solution using a microinjection pump was then maintained until the end of the 3-, 6-and 12-h observation period in the corresponding groups.…”
Section: Preparation Of Animal Models and Associated Therapeutic Regimenmentioning
confidence: 99%
“…For rats in sham-operated groups, common bile duct was only dissociated but not ligated, and a layered suture of the abdominal wall was also performed to close the abdominal cavity. An intraperitoneal injection of Salvia miltiorrhizae injection at a dose of 0.2 ml/100g/day [30,33] was given to rats in the treated groups while equal volume of physiological saline solution was used in the sham-operateds and model control groups. Injection was maintained until the end of the 7-, 14-, 21-and 28-day observation period in the corresponding groups.…”
Section: Preparation Of Animal Models and Associated Therapeutic Regimenmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) offers a plethora of treatment options for complex diseases (Zhang et al, 2009;Wang et al, 2010;Efferth and Koch, 2011). Because the efficacy of TCM is based on the combined effects of its constituents, variation in chemical composition between batches of TCM has always been the deterring factor in achieving consistency in efficacy (Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Through decreasing the level of inflammatory mediators, improving microcirculation and removing oxygen free radicals, Salvia miltiorrhizae injection is able to provide a multi-channel, multi-level and multi-link protection against multi-organ damage caused by SAP or OJ [11][12][13][14][15]. Huang XL et al [16] have found that Salvia miltiorrhizae has a protective effect against lung injury occurring during SAP, whereas no reports concerning the protective effect of Salvia miltiorrhizae on the lungs during OJ are seen.…”
Section: Introductionmentioning
confidence: 99%